Religiosity for Promotion of Behaviors Likely to Reduce New HIV Infections in Uganda: A Study Among Muslim Youth in Wakiso District - Kagimu, Magid; Guwatudde, David; Rwabukwali, Charles; Kaye, Sarah; Walakira, Yusuf; Ainomugisha, Dick (Journal of religion and health, 2013)
The study was done to determine the association between religiosity and behaviors likely to reduce new HIV infections among 1,224 Muslim youth. Respondents with Sujda, the hyperpigmented spot on the forehead due to prostration during prayers, were more likely to abstain from sex, be faithful in marriage, and avoid alcohol and narcotics. Males wearing a Muslim cap were more likely to abstain from sex and avoid alcohol and narcotics. Females wearing the long dress (Hijab) were also more likely to avoid alcohol. This data should be used by stakeholders in promoting behaviors likely to reduce new HIV infections among Muslims.
Keywords: Religiosity; HIV infections; Muslim youth; Uganda; Behaviors